Direct Detection of Viable but Non-culturable (VBNC) Salmonella in Real Food System by a Rapid and Accurate PMA-CPA Technique - Ou, Aifen; Wang, Kan; Ye, Yanrui; Chen, Ling; Gong, Xiangjun; Qian, Lu; Liu, Junyan (Frontiers in Microbiology, 2021)
Salmonella enterica is a typical foodborne pathogen with multiple toxic effects, including invasiveness, endotoxins, and enterotoxins. Viable but nonculturable (VBNC) is a type of dormant form preserving the vitality of microorganisms, but it cannot be cultured by traditional laboratory techniques. The aim of this study is to develop a propidium monoazide-crossing priming amplification (PMA-CPA) method that can successfully detect S. enterica rapidly with high sensitivity and can identify VBNC cells in food samples. Five primers (4s, 5a, 2a/1s, 2a, and 3a) were specially designed for recognizing the specific invA gene. The specificity of the CPA assay was tested by 20 different bacterial strains, including 2 standard S. enterica and 18 non-S. enterica bacteria strains covering Gram-negative and Gram-positive isolates. Except for the two standard S. enterica ATCC14028 and ATCC29629, all strains showed negative results. Moreover, PMA-CPA can detect the VBNC cells both in pure culture and three types of food samples with significant color change. In conclusion, the PMA-CPA assay was successfully applied on detecting S. enterica in VBNC state from food samples.